Teacher's Use of Written Corrective Feedback for Students' Writing Errors - Utami, Sekar Intan; Arianti, Theresia (Foremost Journal, 2023)
Teachers offer corrective feedback to boost students' motivation. The importance of this study is because corrective feedback in education has an important role because students can find out the errors in writing English. Previous studies have examined Written Corrective Feedback in students’ writing. However, none had conducted a study on this topic at the school where the current study was conducted. This is the gap fulfilled by this study. This study aims to find out the types of student errors in English writing at a Junior High School in Jakarta and to find out the types of Written Corrective Feedback that are often used by the teachers there. This study used descriptive qualitative research methods. This study reveals that there are 13 types of errors found in students’ writing, which are singular-plural, word form, word choice, verb tense, adding a word, omitting a word, word order, incomplete sentence, spelling, punctuation, capitalization, article, and meaning not clear. The findings also reveal that Direct Corrective Feedback is the type of feedback that is mostly used by the teachers to correct students’ errors. It is hoped that future studies could elaborate more on the reasons why teachers prefer a particular type of Written Corrective Feedback.